Evaluation of awareness and performance towards COVID-related disinfectant use among the university communities in Lebanon - Wissam Ghach; Jihan Safwan; Racha Kerek; Nisreen Alwan (BMC Public Health, 2023)
Abstract Background The fast spread of COVID-19 reinforced the daily use of disinfectants around the world. However, the awareness gap of disinfectant use could lead to health risks during the prevention of the pandemic. This study aims to assess the level of awareness and performance towards COVID-related disinfectant use among various university communities (student, staff, and faculty) in Lebanon. Methods: A cross-sectional study was conducted between December 2021 and June 2022 among 925 participants (males and females aged between 18 and 64 years old) from academic settings in Lebanese universities using convenience sampling. An online validated survey (score-based questionnaire) of personal disinfectants’ utilization was conducted to evaluate the awareness and performance levels using SPSS (version 21). Mann–Whitney and Kruskal–Wallis tests were used to check significant differences in awareness and performance levels among gender, age, provinces, educational level, university status, and field of study. Friedman test was used to test for significant differences in performance level questions pre-and post-COVID-19. The Spearman correlation test was used to determine the correlation between the awareness and performance of the respondents regarding the use of disinfectants. Results: It was found that the majority of the respondents showed a weak level of awareness (70.8%) while their performance (61.9%) was moderate. Spearman’s correlation analysis concluded a weak correlation between the awareness and performance levels (p < 0.01). The Mann–Whitney test indicated that there was a significant difference (p < 0.05) in awareness and performance levels between males and females. Another notable variable was the educational level of the respondents (p < 0.05) with postgraduate degrees holders recording higher mean scores of awareness than the ones with undergraduate and high school degrees as per Kruskal–Wallis test. Significant differences were shown in awareness scores among the age groups and in performance scores among the field of study (p < 0.05). Conclusions: The study findings highlighted the necessity of awareness campaigns and training programs addressing the technical handling of disinfectants among the communities in Lebanon. Lebanese governmental authorities (Ministry of Public Health, MoPH, and Ministry of Education and Higher Education, MEHE), and the healthcare professionals and public health researchers in Lebanon may utilize this new evidence to initiate public health interventions as a part of the United Nations (UN) sustainability goal of wellbeing (Sustainable Development Goal 3, SDG 3).